Chromosome aberrations in lymphocytes of persons exposed to an earthquake in Armenia - Nersesyan, Armen K.; Boffetta, Paolo; Sarkisyan, Tamara F.; Zalinyan, Gayane G.; Arutyunyan, Rouben M. (Scandinavian Journal of Work, Environment & Health, 2001)
' ' OBJECTIVES ': 'This study attempted to determine the level of chromosome aberrations in lymphocytes of victims of the 1988 earthquake in Armenia. ' ' METHODS ': 'Chromosome aberrations were measured in blood samples taken from 41 victims of the earthquake that hit Armenia in 1988 and in samples of 47 reference blood donors. The victims suffered from severe psychoemotional stress but were otherwise healthy. All the samples were taken 2 to 3 weeks after the earthquake. All the subjects were lifetime nonsmokers. The cells were scored blind as to the exposure status. ' ' RESULTS ': 'The subjects exposed to the earthquake had a higher proportion of cells with chromosome aberrations [3.1 (SD 2.1)%] than the referents [1.7 (SD 1.3)%, P-value for the difference 0.0009]. The difference persisted when the values were adjusted for age and gender [relative risk (RR) 1.9, 95% confidence interval (95% CI) 1.4-2.5]. The difference was present for double breaks (RR 4.1, 95% CI 2.6-6.4), but not for single breaks (RR 1.1, 95% CI 0.8-1.7). The exposed subjects also had a lower percentage of cells with 46 chromosomes (P=0.03) than the referents. ' ' CONCLUSIONS ': 'This study suggests an increase in chromosome aberrations in the lymphocytes of victims of a severe earthquake as compared with the levels of referents. If not due to bias or confounding, the difference may reflect the effect of either environmental exposures related to the earthquake or severe psychogenic stress. The levels of chromosome aberrations found among the earthquake victims in this study are comparable with those found in prospective studies of long-term cancer risk.
Keywords: Armenia; chromosome aberration; earthquake; exposure; lymphocyte; psychogenic stress